An Assessment of the Performance Management System of Asian Institute of Maritime Studies: Basis for System Automation and Integration Plan in the Human Resource Integrated System (HRIS) - Garbin, Marvin M. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
Performance management is a structured approach aimed at enhancing individual and organizational performance to meet desired objectives. This process involves various strategies, tools, and activities to align employee performance with overall organizational goals. The Asian Institute of Maritime Studies (AIMS) also employs its Performance Management System (PMS) to improve employee engagement, productivity, and job satisfaction while driving organizational success. However, manual operation of AIMS' PMS has revealed areas needing enhancement, affecting measurement accuracy and completeness. The process initiates an endless cycle of follow-ups. To address these challenges, the study aims to evaluate AIMS' existing PMS and provide a foundation for its automation and integration within the Human Resource Integrated System (HRIS). By automating the PMS, AIMS aims to decrease manual effort, enhance accuracy and consistency, enable data-driven decisions, and create a user-friendly experience. The study employed a descriptive-survey design, targeting Deans, Directors, Program Chairs, and Department Heads at AIMS. Out of 60 targeted participants, 36 responded. A four-part online survey collected data, assessing respondent profiles, PMS documentation, the actual system, and soliciting improvement suggestions. Weighted mean analysis was used to evaluate scores from each variable. Findings indicate agreement with PMS Documentary Report and System criteria in Parts 2 and 3. However, weighted means are slightly below the average agreement level of 4. Notably, gaps are prominent in Part 4, where respondent suggestions highlight areas for improvement based on user experiences. As a result, it's recommended to proceed with automating the Performance Management System, and integrating it into the HRIS.